Testing Of Lipstick Preparations From Senggani Flower Extract (Melastoma malabathricum L) As A Natural Dye With Various Variations In VCO Concentrations - Dewi, Betna; Fauziah, Dewi Winni (SINTA Journal (Science, Technology, and Agricultural), 2024)
Lip dye is a cosmetic preparation that can provide attractive color to the lips, Senggani flowers have an attractive color so they are suitable for natural dyes on the lips Lipstick formulations use VCO variations with various concentrations. The extraction method was by maceration method. The physical evaluation of lipstick includes Organoleptis test, Homogeneity test, pH test, Strength check, Melting point test, Irritation test, Hedonic/Panelist test.The research data showed that the formulation of lipstick preparations from senggani flower extract (Melastoma malabathricum L) as a natural dye with various variations in VCO concentration could affect the physical properties of lipsticks.